Confrontment and solution to gonadotropin resistance and low oocyte retrieval in in vitro fertilization for type I BPES: a case series with review of literature - Yiqi Yu; Mengxia Ji; Weihai Xu; Ling Zhang; Ming Qi; Jing Shu (BMC, 2021)
Abstract Background FOXL2 mutations in human cause Blepharophimosis, ptosis, and epicanthus inversus syndrome (BPES). While type II BPES solely features eyelid abnormality, type I BPES involves not only eyelid but also ovary, leading to primary ovarian insufficiency (POI) and female infertility. Current mainstream reproductive option for type I BPES is embryo or oocyte donation. Attempts on assisted reproductive technology (ART) aiming biological parenthood in this population were sparse and mostly unsuccessful. Case presentation Two Chinese type I BPES patients with low anti-müllerian hormone (AMH) and elevated follicle stimulating hormone (FSH) presented with primary infertility in their early 30s. Genetic studies confirmed two heterozygous duplication mutations that were never reported previously in East Asian populations. They received in vitro fertilization (IVF) treatment and both exhibited resistance to gonadotropin and difficulty in retrieving oocytes in repeated cycles. Doubled to quadrupled total gonadotropin doses were required to awaken follicular response. Patient 1 delivered a baby girl with the same eyelid phenotype and patient 2 had ongoing live intrauterine pregnancy at the time of manuscript submission. Conclusions This is the second reported live birth of biological offspring in type I BPES patients, and first success using IVF techniques. It confirmed that ART is difficult but feasible in type I BPES. It further alerts clinicians and genetic counsellors to type female BPES patients with caution in view of the precious and potentially narrowed reproductive window.